The Influence of Transformational Leadership Style and Organizational Culture on Employee Performance through Work Motivation in the Secretariat Denpasar City Region - Ida Ayu Chandra Lestari; I Gusti Ayu Wimba; Ida Ayu Putu Widani Sugianingrat (UNHI Press, 2024)
Purpose- To analyze the influence of transformational leadership style and organizational culture on employee performance through work motivation in the Secretariat Denpasar City Region Methodology- The population in focus are employees at the regional secretariat in Denpasar City. The sampling technique uses saturated sampling or census. Therefore, the research objects used were 104 employees of the Regional Secretariat in Denpasar City. The analysis in this study uses a path equation model SEM. Findings- The results of this research indicate that transformational leadership style and organizational culture have a positive effect on the performance and work motivation of Denpasar City Regional Secretariat employees. The transformational leadership style has a positive effect on employee performance through work motivation at the Denpasar City Regional Secretariat. Organizational culture has no effect on employee performance through work motivation at the Denpasar City Regional Secretariat.